Frontera madre(hood): brown mothers challenging oppression and transborder violence at the U.S.-Mexico border - Bejarano, Cynthia L.; Morales, Maria Cristina; Téllez, Michelle (The feminist wire books, 2024)
"Reflecting on the concept as both a methodological and theoretical framework, this collection embodies the challenges and resiliency of mothering along both sides of the U.S.-Mexico border. More than thirty contributors examine how mothering is shaped by the geopolitics of border zones, which also transcends biological, sociological, or cultural and gendered tropes regarding ideas of motherhood, who can mother, and what mothering personifies"--